PENGARUH KESADARAN HALAL, GAYA HIDUP, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SHOPEE FOOD - Fuadah, Aulia Tsamrotul; Ghozali Maski (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The dominating Muslim population in Indonesia and the increase in the number of products that have been halal certified have not been able to describe the consumption behavior of Muslims to be more selective in ensuring the halalness of a product. The purpose of this study is to research and analyze the influence of halal awareness, lifestyle, and product quality on Muslim consumers' decisions on the food delivery service application Shopee Food. The samples obtained were 120 respondents. The analytical tests used are data instrument quality tests, coefficient of determination (R2), classic assumption test, principal component regression analysis with a confirmatory factor analysis approach, t test, and F test. The results of the analysis state partially and simultaneously the variables of halal awareness, lifestyle , and product quality has a significant positive effect on purchasing decisions in the Shopee Food application.